Uso del analisis bivariado para presentar, analizar e interpretar datos provenientes de cultivos asociados - Moreno B., A. (International Center for Tropical Agriculture, 1990)
The application of bivariate analysis to data registered in intercropping systems, in this case cassava and maize, is presented; this method estimates the variation among exptl. materials and the variation among treatments. The application of significance tests and graphic analysis to these data is also indicated. (CIAT)